Social tension : the paradox of Malaysian online journalism / Rahmat Ghazali - Ghazali, Rahmat (Centre for Media and Information Warfare Studies, 2008)
Online journalism has bestowed Malaysians with more democratic space when it is exempted from the Printing Presses and Publication Act 1987 that liberated it from the licensee procedures. Strengthening such freedom, the Communication and Multimedia Act (CMA) 1998, and the Bill of Guarantees of the Multimedia Super Corridor, have ensured that the government would not allow any act of censorship of the Internet. The freer environment had brought online journalism on a different track as compared to that of the mainstream mass media. As a matter of fact the inauguration of the CMA 1998 had marked the plunge of the mainstream presses readership. It also extensively advocates social and political criticisms, which were never before seen in the mainstream mass media. However, the current development projects that online journalism has turned out as contributory to social tension, where irresponsible pieces of journalistic discourse, discussions and debates had apparently inflamed the undercurrents of social and political discontentment. The freer environment also exposes online journalism to emotional and filthy statements that would be fatal to sound interethnic relation when they provoke racism and religious sentiments. In such light, the democratic space of online journalism also advocates a paradox to Malaysian social and political milieus.